Glutamine-stimulated amino acid and peptide incorporation in Bacteroides melaninogenicus. - Lev, M (1980)
The uptake of a number of amino acids and dipeptides by cells and spheroplasts of Bacteroides melaninogenicus was stimulated by the presence of glutamine; 50 mM glutamine induced maximum uptake of glycine or alanine, and glutamine stimulated the uptake of glycine over a wide concentration range (0.17 to 170 mM). Glutamine stimulated the uptake of the dipeptides glycylleucine and glycylproline at significantly faster rates compared with glycine and leucine. The amino acids whose uptake was stimulated by glutamine were incorporated into trichloroacetic acid-precipitable material, and the inclusion of chloramphenicol or puromycin did not affect this incorporation. The uptake of glutamine by cells was concentration dependent. In contrast, in the absence of chloramphenicol 79% of the glutamine taken up by cells supplied with a high external concentration (4.4 mM) was trichloroacetic acid soluble. Glutamate and alpha-ketoglutarate were identified in the intracellular pool of glutamine-incubated spheroplasts. The amino acids and peptides were incorporated into cell envelope material, and a portion (30 to 50%) of the incorporated amino acids could be removed by trypsinization or treatment with papain. The effect of glutamine was depressed by inhibitors of energy metabolism, suggesting that glutamine-stimulated incorporation is an energy-mediated effect.